Chromobacterium violaceum: a fatal case in the northeast of the Brazil - Maria José de Britto Costa Fernandes; Kleber Giovanni Luz; Leonardo de Albuquerque Dantas; Maria Celeste Nunes de Melo; Dulce Almeida (Sociedade Brasileira de Patologia Clínica, 2014)
Chromobacterium violaceum is a rare pathogen that can potentially cause fatal infections in humans. An 8-year-old child from Natal, northeast of Brazil, presented history of fever, sore throat, and abdominal pain, during 5 days before admission, and died 4 hours after hospitalization. Chromobacterium violaceum was isolated from oropharynx scrapings and was resistant to ampicillin, cefotaxime, cefalotin, ceftazidime, and ceftriaxone.